Pengaruh Transformasi Digital dan Bisnis Online Terhadap Pola Perilaku Masyarakat dalam Menggunakan M-Banking Syariah: Studi Kasus pada Masyarakat Martubung - Nadya Fardha Lubis; Riyan Pradesyah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The purpose of this study was to determine the effect of digital transformation and online business on the behavior patterns of the Martubung community in using Islamic M-Banking. Where at this time, many people are worried about using M-banking, because many people are exposed to fraud in using M-banking. Therefore, the study wanted to test the variables of digital transformation and online business development in influencing the interest of the Martubung community in using M-Banking. The sample used in the study amounted to 100 people with the characteristics of sharia M-Banking users. The data obtained is processed using the SPSS 27 application, using multiple linear regression methods. The results obtained that by farsiap or t test, the digital transformation variable affects the behavior patterns of the martubung community using sharia M-Banking. Then the online business variable affects the behavior patterns of the Martubung community using sharia M-Banking. Simultaneously, the Digital Transformation and Online Business variables affect the behavior patterns of the martubung community using sharia M-Banking, amounting to 69.1% and the remaining 30.9% is influenced by other variables not included in the study.